Food safety at home: knowledge and practices among adults in suburban community in Malaysia - Yusof, Muhammad Zubir; Mohd Rus, Razman; Pasi, Hafizah; Abd. Aziz, Karimah Hanim; Hassan, Noor Artika; Ab Rahman, Jamalludin; Nasreen, Hashima E (2018)
Background/Aim Foodborne illness is attributable to improper preparation of foods either at home or food premises. Due to hot and humid climate in Malaysia, it becomes the favourable condition for the growth of foodborne bacteria and contributed the high number of reported cases for food poisoning. Most people unaware that the risk of food poisoning may originate from home is higher than food consumed in the restaurants. Even though there is usually a small outbreaks that come from home, the actual proportion of this outbreaks is likely to be much larger than it has been reported to be. Thus, this study aims to determine the level of knowledge and practices of food safety among adults in sub urban Malaysia living at home. Methods A cross-sectional study was conducted among adults lived in sub urban area located in the east coast of Malaysia. All participants aged between 18 to 65 years old were randomly recruited. Data were collected through a guided self-administered validated questionnaire which consisted of questions regarding knowledge and practices of food safety. Results A total of 390 eligible adults with a mean age of 35.9 years (SD: 9.1) responded to our study (response rate: 68.3%). Majority of them had good knowledge (66.2%) and practices (96.4%). The level of good knowledge was significantly associated with those who had sources of information on food safety ( 2=10.733, p = 0.001). However, there were no significant differences for all sociodemographic factors with their practices. A significant positive relationship between total score of knowledge and practices was also observed (rs = 0.211, p < 0.001). Conclusions Overall, this study demonstrated that food safety knowledge of the adults reflected their good practice towards food handling at home. Findings will help the policy maker to make decision in preventing the foodborne illness.